2019
DOI: 10.1097/sla.0000000000002947
|View full text |Cite
|
Sign up to set email alerts
|

Low Ligation of Inferior Mesenteric Artery in Laparoscopic Anterior Resection for Rectal Cancer Reduces Genitourinary Dysfunction

Abstract: LL of the IMA in LAR + TME results in better GU function preservation without affecting initial oncological outcomes. HL does not seem to increase the anastomotic leak rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 37 publications
8
106
2
1
Order By: Relevance
“…The total number of harvested LNs and the number of positive LNs show no differences between the two groups, which was similar to the results of previous study [33,34]. Furthermore, previous studies have confirmed that low ligation of IMA in laparoscopic anterior resection for rectal cancer reduces genitourinary dysfunction [35]. However, this outcome was not observed in this study, possibly because dissection of the IMA root LNs inevitably injured the superior hypogastric plexus.…”
Section: Discussionsupporting
confidence: 91%
“…The total number of harvested LNs and the number of positive LNs show no differences between the two groups, which was similar to the results of previous study [33,34]. Furthermore, previous studies have confirmed that low ligation of IMA in laparoscopic anterior resection for rectal cancer reduces genitourinary dysfunction [35]. However, this outcome was not observed in this study, possibly because dissection of the IMA root LNs inevitably injured the superior hypogastric plexus.…”
Section: Discussionsupporting
confidence: 91%
“…The intraoperative parameters and postoperative complication rates were important indexes for demonstrating the e cacy of quality control in a surgical procedure. A previous RCT study showed that the LCA preservation or not does not increase the duration of laparoscopic low anterior resection of rectal cancer [10]. Our study revealed the mean operating time of the LCA preservation group was 75 minutes signi cantly longer than that of the LCA non-preservation group.…”
Section: Discussionmentioning
confidence: 42%
“…Nevertheless, preserving the LCA or not during laparoscopic low anterior resection of rectal cancer, is still debated. A randomized multicenter controlled trial showed that low ligation of the IMA in laparoscopic rectal cancer surgery resulted in better genitourinary function preservation without affecting initial oncological outcomes, while high ligation of the IMA did not increase the anastomotic stula rate [10]. However, the effect of high or low ligation of IMA on long-term oncologic outcomes was not reported in this study.…”
Section: Introductionmentioning
confidence: 58%
“…Details of the included studies were collected (Table 1). Seven RCTs [18][19][20][21][22][23][24], 19…”
Section: Study Characteristicsmentioning
confidence: 99%
“…RC/PC studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], and two CC studies [44,45] published between 2011 and 2019 were analyzed, investigating 10,545 patients (including 4920 patients who underwent LCA non-preservation surgery and 5625 patients who underwent LCA preservation surgery) (CRC group). Additionally, 18 studies on RC alone (including 7 RCTs [18][19][20][21][22][23][24] and 11 RC/PC studies [25, 26, 28, 30-32, 35, 38, 39, 42, 43]) with 7142 patients (including 3468 patients who underwent LCA non-preservation surgery and 3674 who underwent LCA preservation surgery) were extracted for the subgroup analysis (RC group). Studies were assessed using the Cochrane and NOS scoring systems.…”
Section: Study Characteristicsmentioning
confidence: 99%